The Role of Non-Governmental Organizations (NGOs) in Law Enforcement and Human Rights - Siska Karina; Razia Khan; Amir Raza (Yayasan Adra Karima Hubbi, 2025)
Background. Non-governmental organizations (NGOs) play a pivotal role in the realm of law enforcement and human rights. In recent decades, their influence has expanded significantly, especially in areas where government action is either insufficient or absent. NGOs often bridge gaps in legal and human rights protection by advocating for vulnerable populations, monitoring abuses, and holding governments accountable. Objective. This study aims to evaluate the role of NGOs in law enforcement and human rights, with a particular focus on their contributions to legal reforms, advocacy for victims, and international collaborations. The research explores how NGOs influence law enforcement mechanisms and contribute to the advancement of human rights protections across different regions. Method. A qualitative research design was employed, utilizing case studies, interviews with NGO leaders, legal experts, and human rights advocates, and document analysis of reports and legal frameworks where NGOs have had significant influence. Results. The study found that NGOs significantly impact human rights law enforcement, especially in regions with weak legal frameworks. They provide essential resources for victims, influence policy changes, and sometimes fill gaps left by state institutions. However, challenges such as limited funding and political resistance affect their effectiveness. Conclusion. NGOs are indispensable in promoting human rights and enforcing laws in under-served regions. Their role should be enhanced through stronger partnerships with governments and international organizations.